Extraction of octacosanol from rice wax (Chemical Method) - Yape, Erlinda Olivar (1994)
Rice bran wax is composed mainly of esters which can be decomposed into two major components: the fatty alcohols and the fatty acids. These components could be obtained by alkali hydrolysis, otherwise known as saponification. The best operating condition in the production of alcohol was established and the fatty alcohol composition was identified by gas chromatography. Octacosanol, a component of the fatty alcohol present in the rice bran wax, was identified by GC-MS and GC. octacosanol was found to be 13% of the fatty alcohols. The octacosanol was purified by recrystallization with acetone and hexane, with the combination of the two solvents as recrystallization solvents being more preferable.